2017
DOI: 10.1175/jcli-d-16-0641.1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the ENSO Teleconnection to the Tropical North Atlantic

Abstract: One of the most robust remote impacts of El Niño-Southern Oscillation (ENSO) is the teleconnection to tropical North Atlantic (TNA) sea surface temperature (SST) in boreal spring. However, important questions still remain open. In particular, the timing of the ENSO-TNA relationship lacks understanding. The three previously proposed mechanisms rely on teleconnection dynamics involving a time lag of one season with respect to the ENSO mature phase in winter, but recent results have shown that the persistence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 55 publications
10
67
1
1
Order By: Relevance
“…Pacific, similar to the Gill-type responses associated to ENSO events (DeWeaver & Nigam, 2002;García-Serrano et al, 2017). Therefore, we conclude that the physical mechanism that forced the event is similar to the mechanism at play during strong positive ENSO phases but located more to the west.…”
Section: 1029/2017jd028019supporting
confidence: 75%
See 1 more Smart Citation
“…Pacific, similar to the Gill-type responses associated to ENSO events (DeWeaver & Nigam, 2002;García-Serrano et al, 2017). Therefore, we conclude that the physical mechanism that forced the event is similar to the mechanism at play during strong positive ENSO phases but located more to the west.…”
Section: 1029/2017jd028019supporting
confidence: 75%
“…The convective processes in WTP region (see supporting information Figure S3) produce diabatic heating in the midtroposphere and result in flow divergence and high pressures at 200 hPa level. In the INI and TROP simulations a Gill‐type response to the anomalous SSTs can bee seen in the western Pacific, similar to the Gill‐type responses associated to ENSO events (DeWeaver & Nigam, ; García‐Serrano et al, ). Therefore, we conclude that the physical mechanism that forced the event is similar to the mechanism at play during strong positive ENSO phases but located more to the west.…”
Section: Retrospective Model Predictionssupporting
confidence: 68%
“…Additionally, ENSO has significant teleconnections to the tropical and subtropical Atlantic (García Serrano et al, ). The large‐scale variability of the tropical Atlantic is governed by so‐called Atlantic Niños, which are connected at a lag of several months to the tropical Pacific ENSO (Latif & Groetzner, ; Lübbecke, ; Lübbecke & McPhaden, ; Lübbecke et al, ) and which are suggested to have a feedback effect onto the tropical Pacific (Rodríguez‐Fonseca et al, ).…”
Section: An Overview Of Enso and Its Tropospheric Teleconnectionsmentioning
confidence: 99%
“…: Brönnimann 2007 and references therein). The tropospheric pathway itself includes four documented different tracks (García-Serrano et al 2017). One of the most recognized tracks is associated with changes in the non-divergent (or rotational) flow and involves a North Pacific-North Atlantic connection through the excitation of a tropical forced wavetrain from the Pacific (describing the Tropical Northern Hemisphere pattern; hereinafter TNH) that propagates into the North Atlantic (e.g.…”
Section: Introductionmentioning
confidence: 99%